Tuberculose Ganglionar em pacientes co-infectados pelo HIV-1: estudo clínico e laboratorial - Nicol, A.F.; Serapião, M.J.; Veloso, V.G.; Pignataro, P.; Cuzzi Maia, T.; Chicarino, J.M.; Silva Júnior, Lapa (Brazilian Journal of Sexually Transmitted Diseases, 1997)
Lymph node tuberculosis is a frequent extrapulmonary form of tuberculosis affecting HIV seropositive patients. ln these cases, histopathologic e/tanges are very different from those seen in immunocompetent individuais. More tltan 70% of cases in different series display alterations in granuloma formation, and in most severe fonns absence of granulomas, accompanied by massive necrosis, decreased numbers of giant and epithelioid cells and large numbers of fast acid bacilli can be found, denoting incomplete or defective immune response against Mycobacterium. We studied clinica[ and laboratory features, including microbiology and histopathology, from a series of 2 7 patients submitted to biopsy for diagnosis of lymplt node conditions. Tlte cases were divided in three groups; Group I (n = 7): lymph node tuberwlosis in HIV negative patients; Group II (n =9): lymph node tuberculosis in HIV positive patients; Group Ili (n= 11): reactive lymphadenopathy associated with HlVinfection. ln the HTV-1 infection, we found the presence of incomplete or absent granulomas, extensive necrosis and large numbers of mycobacteria. These findings suggest that patients coinfected with Mycobacterium tuberculosis and HIV-1 display severe impairment of the immune response that could explain unusual and severe forms of tuberculosis.